Case Report: Genetic profiling of small intestine metastasis from poorly differentiated non-small cell lung cancer: report of 2 cases and literature review of the past 5 years - Wang, Mengqin; Chen, Gang; Luo, Jiang; Fan, Zhipeng; Liu, Yuying; Xie, Conghua; Gong, Yan (Frontiers in Oncology, 2023)
Background: Poorly differentiated non-small cell lung cancer (NSCLC) is characteristic of high rate of distant metastasis and late stages at diagnosis. Small intestine metastasis is a rare but severe complication of lung cancer with a high rate of mortality. However, there is currently a lack of genetic profile studies on the small intestine metastasis of lung cancer. Case presentations: We present 2 cases of male patients in their 60s with primary NSCLC of low differentiation, initially with no distant metastasis detected. Biopsy samples were obtained from the primary pulmonary lesions, and both patients received systematic radiotherapy (RT) and chemotherapy. However, both cases presented with abdominal pain and distension, and immunohistochemistry of small intestine biopsy samples obtained by endoscopy confirmed lung cancer metastasis. Next generation sequencing was used to explore the genetic profiles from the biopsy samples of both the primary pulmonary lesions and small intestine metastases. The correlated genes responsible for the small intestine metastasis from poorly differentiated NSCLC in these 2 patients included TP53, LRP1B, and FGFR2. The reports of small intestine metastasis from poorly differentiated NSCLC with the past 5 years were systematically reviewed and summarized subsequently. Conclusions: Poorly differentiated NSCLC with small intestine metastases, while rare, substantially impacts the prognosis and poses major challenges for diagnosis and treatment. Through comparisons of genetic profiles between patients and in the same patient before and after metastasis, we identified the mutations in genes such as TP53, LRP1B, and FGFR2, which were correlated with the occurrence and progression of poorly differentiated NSCLC, as well as its small intestinal metastasis. This discovery has the potential to guide clinicians in developing personalized treatment plans through the manipulation of targeted and radiation therapies.